The Mixed Type Splitting Methods for Solving Fuzzy Linear Systems. (18th November 2014) - Saberi Najafi, H.; Edalatpanah, S. A.; Shahabi, S.
Abstract : We consider a class of fuzzy linear systems (FLS) and demonstrate some of the existing methods using the embedding approach for calculating the solution. The main aim in this paper is to design a class of mixed type splitting iterative methods for solving FLS. Furthermore, convergence analysis of the method is proved. Numerical example is illustrated to show the applicability of the methods and to show the efficiency of proposed algorithm.